Prevalence and Factors Associated with Severe Anaemia Post-Caesarean Section at a Tertiary Hospital in Southwestern Uganda - Sivahikyako, Sylvie Atosa; Owaraganise, Asiphas; Tibaijuka, Leevan; Agaba, David Collins; Kayondo, Musa; Ngonzi, Joseph; Mugisha, Julius; Kanyesigye, Hamson (Research Square, 2021)
Background: Severe anaemia post-caesarean section adversely affects the woman and the new-born. While prenatal anaemia is extensively studied, the literature on post-caesarean section anaemia is limited and characteristics of women more likely to develop severe anaemia after caesarean section are unknown. This study aimed to determine the prevalence and factors associated with severe anaemia on three post caesarean section. Methods: Women at day three post-caesarean section were consecutively enrolled in a cross-sectional study at Mbarara Regional Referral Hospital. We measured their haemoglobin (Hb) concentration and defined severe anaemia as Hb<7.0 g/dL. We excluded women diagnosed with severe pre-caesarean section anaemia and those who got blood transfusion without pre-transfusion Hb record. We interviewed the women and collected data on sociodemographic, obstetric, and medical characteristics. The primary outcome was severe anaemia post-caesarean section. We used logistic regression analysis to determine independent factors associated with severe anaemia after caesarean section. P-value <0.05 was considered statistically significant. Results: From December 2019 to March 2020, 427 of 431 screened women were enrolled in the study. Their mean age was 26.05 (SD ± 5.84) years. Three hundred thirteen (73.3%) had attended at least four antenatal care visits. The prevalence of severe post-caesarean section anaemia was 6.79 per cent. Fetal macrosomia (aOR 7.9 95%CI: 2.18-28.85, p<0.01) and having mild or moderate anaemia pre-caesarean section (aOR:9.6, 95%CI: 3.91- 23.77, p<0.01) were the factors associated with severe anaemia postcaesarean section. Conclusion: Severe anaemia post-caesarean section commonly occurs and is associated with anaemia preoperatively and delivering a foetus with macrosomia. Preoperative haemoglobin optimization and intraoperative blood conserving measures are imperative among such women to prevent postoperative anaemia—as well as post-caesarean section haemoglobin estimation before discharge from the hospital to detect anaemia early and optimise remedies.
Keywords: Severe anaemia; Day three; Post-caesarean section; Haemoglobin